HAMBATAN DAN TANTANGAN PEMBELAJARAN JARAK JAUH (PJJ) DI SD MUHAMMADIYAH 1 DENPASAR PADA MASA PANDEMI COVID-19 - Najmal Qudsi, Hafshah; Made Wiasti, Ni; Aliffiati, Aliffiati (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
Covid-19 pandemic outbreak has brought major changes to various aspects of life, including the education sector. One of the most significant impacts is the change in the learning process, which was initially carried out face-to-face and then turned into online, which can be done at home through distance learning (PJJ). This change not only has implications for the learning process but also for methods, technology and the role of stakeholders. Learners and educators must adapt to the new system to overcome the barriers and challenges that arise. This study aims to determine the challenges and obstacles in the implementation of distance learning (PJJ) at Muhammadiyah 1 Denpasar Elementary School (SD) during the Covid-19 pandemic. Data collection was carried out using interviews, observations, and literature studies relevant to the problem and then described and interpreted thoroughly using a qualitative research paradigm. The results showed that there are obstacles and challenges in the implementation of distance learning (PJJ) for students at SD Muhammadiyah 1 Denpasar, namely adjusting learning methods with the use of technology and understanding learning materials. The efforts made to minimize this are with the active role between students, parents, and teachers or educators.